Effective electrostatic confinement of polysulfides in lithium/sulfur batteries by a functional binder. (October 2017) - Zhang, Liang; Ling, Min; Feng, Jun; Liu, Gao; Guo, Jinghua
Abstract: Lithium/sulfur (Li/S) batteries have been recognized as one of the most promising substitutes for current energy-storage systems due to their high-energy density and low cost. However, the high solubility of intermediate products ( i.e., lithium polysulfides) and the resultant shuttle effect lead to a rapid capacity fading along with a low Coulombic efficiency, which hinders the practical application of Li/S batteries. Herein, polyethylenimine (PEI) polymer is applied as a polar binder in Li/S batteries to address above issues. The sulfur cathode with a high sulfur loading density of 8.6 mg/cm 2 coated by an ultrathin PEI layer (~ 6.9 nm) shows a high initial areal capacity of up to 9.7 mAh/cm 2 . The capacity is still maintained at 6.4 mAh/cm 2 after 50 cycles, which is comparable to that of commercial Li-ion batteries. The excellent cycling performance is attributed to the presence of abundant amino groups in PEI polymer, which can strongly bond with the intermediate lithium polysulfides through electrostatic force and therefore suppress the shuttle effect, as revealed by in situ / operando ultraviolet-visible spectroscopy and S K-edge X-ray absorption spectroscopy. Our effective strategy of immobilizing lithium polysulfides by electrostatic force through a functional binder should be of great significance for the practical application of Li/S batteries. Graphical abstract: Highlights: An areal capacity of 6.4 mA h/cm 2 is achieved by commercial sulfur and PEI binder. The abundant amino groups in PEI form strong electrostatic interaction with LiPSs. The strong interaction is verified by in situ/operando UV-vis and XAS.